Implementasi Karakter Pendidikan Islam di SD Negeri Percontohan Karang Baru Aceh Tamiang - Afrida, Nina; Sembiring, Masdalifah; Hidayani, Nurul (Diksi: Jurnal Pendidikan dan Literasi, 2023)
The aim of this article is to describe the process of applying Islamic education in SD Negeri 1 Percontohan Aceh Tamiang. Qualitative was applied as the approach using ethnography in 60 days of observation. To collect the data, the researcher observed 10 students of SD 1 Percontohan Aceh Tamiang. While Miles and Hubberman’s data analysis was used. The result showed that the implementation of Islamic characters in SD Negeri 1 Percontohan was running well. There are four forms, they are faith, worship, Akhlak, and achievement.